Deficiency of ataxia‐telangiectasia mutated kinase attenuates Western‐type diet‐induced cardiac dysfunction in female mice. Issue 18 (19th September 2022) - Wingard, Mary C.; Dalal, Suman; Shook, Paige L.; Ramirez, Paulina; Raza, Muhammad U.; Johnson, Patrick; Connelly, Barbara A.; Thewke, Douglas P.; Singh, Mahipal; Singh, Krishna
Abstract: Chronic consumption of Western‐type diet (WD) induces cardiac structural and functional abnormalities. Previously, we have shown that WD consumption in male ATM (ataxia‐telangiectasia mutated kinase) deficient mice associates with accelerated body weight (BW) gain, cardiac systolic dysfunction with increased preload, and exacerbation of hypertrophy, apoptosis, and inflammation. This study investigated the role of ATM deficiency in WD‐induced changes in functional and biochemical parameters of the heart in female mice. Six‐week‐old wild‐type (WT) and ATM heterozygous knockout (hKO) female mice were placed on WD or NC (normal chow) for 14 weeks. BW gain, fat accumulation, and cardiac functional and biochemical parameters were measured 14 weeks post‐WD. WD‐induced subcutaneous and total fat contents normalized to body weight were higher in WT‐WD versus hKO‐WD. Heart function measured using echocardiography revealed decreased percent fractional shortening and ejection fraction, and increased LV end systolic diameter and volume in WT‐WD versus WT‐NC. These functional parameters remained unchanged in hKO‐WD versus hKO‐NC. Myocardial fibrosis, myocyte hypertrophy, and apoptosis were higher in WT‐WD versus WT‐NC. However, apoptosis was significantly lower and hypertrophy was significantly higher in hKO‐WD versus WT‐WD. MMP‐9 and Bax expression, and Akt activation were higher in WT‐WD versus WT‐NC. PARP‐1 (full‐length) expression and mTOR activation were lower in WT‐WD versus hKO‐WD. Thus, ATM deficiency in female mice attenuates fat weight gain, preserves heart function, and associates with decreased cardiac cell apoptosis in response to WD. Abstract : Deficiency of ataxia telangiectasia mutated kinase (ATM) in humans increases the risk of ischemic heart disease. Previously, we provided evidence that Western‐type diet in male ATM deficient mice accelerates body weight gain, induces systolic dysfunction with increased preload, and exacerbates cardiac hypertrophy, apoptosis, and inflammation. Here, we provide evidence that ATM deficiency associates with attenuated fat weight gain, and plays a cardioprotective role with preservation of heart function and decreased cardiac cell apoptosis in female mice fed with Western‐type diet. Further investigations of sex‐specific role of ATM in Western‐type diet‐induced cardiac functional and structural changes may help elucidate the appropriate sex‐specific treatment and nutritional counseling for patients with ATM deficiency.